Strategi Pemasaran Produk Tortila Jagung - Satyajaya, Wisnu; Rangga, Azhari; Marniza, Marniza (Journal of Food and Life Sciences, 2017)
One of the corn products which able to increase its economic value is corn tortilla. The housewives joining the women farmer’s community take an initiative to develop the corn tortilla product. This activity has been done since 2013 by Kemuning II.  However, the trouble comes due to they did the common strategy while the competition between MSME getting more strict.  Therefore, it is required a precise marketing strategy to overcome such kind of this problem.This research intended to identify the strength, weaknesses, opportunity, threats, and to find the suitable marketing strategy of the corn tortilla product.  This research used QSPM analysis which was resulted from matrix of IFE, EFE, IE and SWOT matrix.  Based on the results, the study showed that the greatest strengths of the business belonging to Kemuning II WFC are:  (1) raw materials were very abundant with a score of 0.258, (2) the main weaknesses was not having a promotion media with a score of 0,071, (3) the main opportunity was a guidance from the government with a score of 0.209, (4) and the main threat was the change of weather being unstable with a score of 0.133.  The rating of IE matrix placed MSME at the cell position V, those were holding and maintaining strategies. The strategy prioritized for the business of Kemuning II was to improve the internal management system by improving work motivation and promotional activities to expand the marketing area. Keywords:  MSME, tortilla, marketing strategy, SWOT, QSPM